Antibiotics Resistant Pattern of Bacteria Isolated from Spoiled Avocado Fruit Sold in Sokoto Metropolis - Adamu Almustapha Aliero; Felicia Yakubu Turba; Ahmad Ibrahim Bagudo; Abdul’azeez Aishat Folake; Sule Sahabi Manga (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Consuming fruit contaminated with bacteria remains a crucial route of foodborne infection in developing countries and creates a severe public health burden. The research aimed to determine the antibiotic-resistant pattern of bacteria associated with the spoilage of Avocado pear (Persea americana) sold in the Sokoto metropolis. Twenty spoilt avocado fruits were obtained from market three in Sokoto Metropolis. The bacteriological analysis was carried out using the pour plate method. The antibiotic resistance pattern was determined using the Kirby-Bauer disk diffusion method. A total of five species of bacteria were isolated and identified in this study. The mean and standard error of total viable bacterial counts of avocado samples across three different locations ranged from 4.20±5.77 to 8.43±33.49 (x 104CFU/g). A total of 19 bacterial isolates were identified from avocado samples. Staphylococcus aureus had the highest frequency of occurrence, 16 (29.2%), while Klebsiella sp. had the lowest frequency of occurrence, 7 (12.7%). Among all antibiotics tested against bacterial species, Escherichia coli isolates were found to have 10 (91%) and 9 (82%) resistance against ciprofloxacin and streptomycin, respectively. Pseudomonas sp. was found to be 100% resistant to chloramphenicol and Septrin (cotrimoxazole). However, S. aureus was found to have 12 (72%) resistance to pefloxacin. Similarly, Klebsiella spp. were found to be 7 (100%) resistant to Septrin. Isolation of these bacterial species, especially E. coli from avocado samples analyzed, is of public health significance, especially the presence of antibiotic resistance species.